Quality of Life of the Patient with Head and Neck Cancer Submitted to Radiotherapy and the Overload of Their Caregivers - Delalibera,Daniela (2021)
Abstract Introduction Esthetic and functional changes are frequent in patients with head and neck cancer, and they can be caused by both tumor and treatment. Physical and functional impairment often requires the need of a caregiver, who may feel overwhelmed with the tasks of care. Objective This study aims to evaluate the quality of life of patients with head and neck cancer submitted to radiotherapy and the overload of their caregivers. Methods This is a quantitative cross-sectional study with 42 patients with head and neck cancer and 17 caregivers evaluated during the radiotherapy treatment. Patients responded to the following questionnaires: Functional Assessment of Cancer Therapy for Head and Neck Cancer (FACT-H&N) and Shame and Stigma Scale (SSS), while the caregivers responded to the Zarit Burden Interview Scale (ZBI) and Palliative Performance Scale (PPS). Results Head and neck cancer patients showed a decline in the quality of life in all FACT-H&N domains, with the domain of additional concerns having the worst outcome. Among the feelings reported by patients, the most important was penitence. Less than half of the patients needed caregivers. It was observed that the greater the degree of commitment of the patient, the greater the degree of overload of the caregiver. Conclusion Therefore, the quality of life of the patient with head and neck cancer is an important aspect to be considered during the therapeutic choice and in the follow-up of the patient, since it has influenced both the patient and his caregiver.